Design of SMACA: synthesis and its analysis through rule vector graph for web based application. (1st December 2008) - Kundu, Anirban; Dutta, Ruma; Mukhopadhyay, Debajyoti
Web search engine uses indexing for management of web-pages in a mannered way. Web-pages are well distributed within the database of server. Both forward and inverted indexing is employed to tackle web-pages as a part of its functional design. This indexing mechanism helps in retrieving data from the database based on user query. In this paper, an efficient solution to handle the indexing problem is proposed with the introduction of non-linear single cycle multiple attractor cellular automata (SMACA). This paper also reports an analysis on SMACA using rule vector graph (RVG). This work simultaneously shows generation of SMACA by using specific rule sequence. Searching mechanism is done with O(n) complexity. SMACA provides an implicit memory to store the patterns. Search operation to identify the class of a pattern out of several classes boils down to running a cellular automata (CA) for one time step. This demands storage of the CA rule vector (RV) and the seed values. SMACA is based on sound theoretical foundation of CA technology.